Life comes first, but lifestyle also matters: aesthetic responses to pandemic angst - Pussetti, Chiara (2023)
The beauty industry has largely been considered recession-proof. However, lockdowns dictated by the pandemic have brought significant changes to our selfcare routines. Is aesthetic surgery perceived by consumers as a strategy to cope with anxiety, enhance lives inside and out, and increase dignity, happiness, and self-esteem? How do we want to look aesthetically after social distancing measures have been lifted? Are the specific conditions of the present moment linked to the prospect of increased competition? Personal anxieties, motives and desires resist simple quantification and are often dismissed or overlooked in economic literature. Ethnography provides a possibility for a different approach, creating a better understanding of consumers’ emotional and behavioural responses to the Coronavirus outbreak.